Capital Markets and Corporate Governance in Colombia (2009)
This paper analyses the long term trends in Colombia's capital market development and corporate governance implementation by large public corporations. In that sense, it discusses the historical pattern of corporate governance in the country both regarding legal regime and companies' practices: Corporate governance practices commonly adopted by security issuers including features related to transparency. The paper also analyzes the recent corporate governance reforms, the performance of capital market, and identifies the major drivers and constraints to firm's equity capital financing and capital market deepening. Among them it can be highlighted the role of the IPOs associated with the privatized state owned companies during the nineties and the effects of the mergers and acquisitions that has taken within the main business groups that have reinforced firm delisting and migration patterns. Regarding the financial sector the paper analyzes the effect of the 1993 financial reform on the banking ownership structure, the public debt and fixed income market, and the role of pension funds. The paper's main conclusion is the need of equity market deepening to sustain the steady growth of the pension funds capitalization system in the country.